On gymnastics frontier technical creations - Liang, C.; Tian, M. (2003)
Gymnastics techniques can be viewed as a pyramid with many layers. The base of the pyramid is the broad structure upon which basic techniques are first learned and then applied to the accumulation of more advanced skills. The most advanced competitive state - i.e. the spire of the pyramid - is what we call the frontier techniques (FT). "Innovation is life, and high difficulty elements make champions" has been regarded as the basic developmental law of gymnastics. One of the reasons why some gymnastic powers have achieved outstanding success in world competitions is that their gymnasts have the courage to try the most frontier techniques. From the Code of Points we can find that many elements are named after these gymnasts. In international gymnastics competition, only by mastering more frontier elements and completing with higher quality can gymnasts experience success on the world gymnastics stage. This paper tries to probe the theory of frontier technique creations on frontier technical long wave, joint district of frontier technique expansion and frontier technical difficulty developmental rate.